Normalising the use of electronic evidence - Elena Alina Ontanu (Oñati Socio-Legal Series)
Society is increasingly relying on technology for daily business and activities. This is linked to a rapid update in technology use and digitalisation with courts being called to consider new forms of evidence in an electronic environment and/or rely on technology for the taking of evidence. The normative framework concerning electronic evidence remains fragmented while various legislative projects are ongoing. In this process the global pandemic accelerated attention for technology solutions and their integration in the handling of court claims. In the EU, the reviewed Taking of Evidence Regulation (Regulation 2020/1783) addresses some of the necessary aspects related to electronic evidence and cooperation between authorities. Other elements are covered by cross-sectorial EU legislation such as regulations concerning data protection or electronic identification and trust services. New regulation proposals concerning the digitalisation of judicial cooperation and communication in cross-border procedures are set to address some of the legislative gaps in the near future as well as support the developments of necessary technology. However, the overall existing legislation is only partly sufficient for providing a comprehensive framework and does not provide much guidance in the process of considering metadata or assessing electronic evidence.